Особливості відшкодування шкоди як способу захисту прав інтелектуальної власності - Ківалова, Тетяна Сергіївна; Кивалова, Татьяна Сергеевна; Kivalova, T. (My University, 2010)
The article is devoted to the features of damages compensation as a method of intellectual property rights protection. The emphasis in the article is paid to the civil-law intellectual property rights protection. The content, grounds and conditions of compensation of property damage and compensation for moral injury are investigated. The current legislation of Ukraine is analyzed in the article. The mechanism of realization of right to damages compensation caused to subjects of intellectual property rights is disclosed.
Ківалова Т. С. Особливості відшкодування шкоди як способу захисту прав інтелектуальної власності / Т. С. Ківалова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 16-26.
Keywords: відшкодування шкоди як способу захисту прав інтелектуальної власності; право інтелектуальної власності; возмещение ущерба как способа защиті прав интеллектуальной собственности; право интеллектуальной собственности; reparations as a way zaschitі intellectual property rights; intellectual property rights